MANAJEMEN BANK SAMPAH MANDIRI SEJAHTERA SEBAGAI KEGIATAN EKONOMI UMAT DI MASA COVID-19 DI KELURAHAN PEDURENAN KOTA BEKASI - Rinovian Rais (Institut Bisnis Muhammadiyah Bekasi, 2022)
The strategy of implementing 3R (Reuse / Reuse), (Reduce / Reduce), (Recycle / Recycle) in independent waste banks is a prosperous form of waste management at existing sources at the community level with the economic incentive pattern of the people during the Covid-19 period Bank Sampah Mandiri Sejahterah RW 013 Pedurenan, Mustika Jaya District, Bekasi City has existed since 2015 and has been around until now as a continuous activity in Bekasi City. The KKN in the Pedurenan Village has the aim of being able to influence public participation in saving at Bank Sampah Mandiri Sejahterah RW 013 Kelurahan Pedurenan, Mustika Jaya District, Bekasi City. This study used a descriptive qualitative approach in Pedurenan District, Mustika Jaya District, and Bekasi City. The data is collected using a direct observation system, asking and answering questions with the manager, and documenting the photos around the Mandiri Sejahtera waste bank all of these data are processed and described using a qualitative descriptive method, and the results of his research through this SWOT analysis show the sustainability aspects of the independent waste bank. in RW 013 Kelurahan Pedurenan, Mustika Jaya Subdistrict, Bekasi City, it is at the 70% level where the used goods storage system in the waste bank is deemed to meet fairness requirements. Where there are seven influential groups who have an interest in an independent waste bank to prosper. It has the role of the Bekasi City Environmental Service, Bekasi District Government, Pedurenan Village Government, waste bank customers, collectors, scavengers, and the community around RW 013 Pedurenan Village. The main strategy used.